Does University Type Affect Wage Returns? Instrumental Variable Evidence - Rahayu Nurhidayah Haris; Muhammad Furqan; Sugiarti Yusuf (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: This study examines whether university type—public versus private—influences graduates’ wage outcomes. It addresses a central policy question on how institutional differences shape labor market returns and inequality in higher education. Design/Methods/Approach: Using pooled cross-sectional data from the Indonesian Family Life Survey (IFLS) waves 4 (2007) and 5 (2014), the analysis focuses on bachelor’s degree holders in wage employment. To mitigate endogeneity, both Ordinary Least Squares (OLS) and Instrumental Variable (IV) estimation are employed, with public university admission system reforms across cohorts serving as instruments. Findings: OLS results indicate that public university graduates earn 12.6%–25.2% more than their private counterparts, while IV estimates reveal larger premiums—89.5% in 2007, narrowing to 26.9% in 2014. Age-cohort analysis shows substantial advantages for younger graduates, particularly those aged 21–35, while differences become statistically insignificant among individuals aged 36 and above. Originality/Value: This study contributes new causal evidence on institutional heterogeneity in educational returns, an underexplored context in the global literature. By applying robust econometric techniques, it advances understanding of how institutional background interacts with labor market outcomes. Practical/Policy implication: The findings highlight the importance of institutional quality in higher education. Policymakers should prioritize reducing disparities between public universities and private universities to promote equitable access, improve labor market integration, and strengthen the efficiency of public investment in education.